ナンキョク チイキ カンソク ヨウ タテモノ JARE-65 ハツデントウ ギジュツ ホウコク - 樋田, 直人; ヒダ, ナオト; 鈴木, 孝久; スズキ, タカヒサ; HIDA, Naoto; SUZUKI, Takahisa (国立極地研究所, 1965)
P(論文) A newly designed generator hut which will become the heart of the Japanese Antarctic Research Expedition's Syowa Station was completed recently. The generator hut has a floor space of 68.8 square meters and contains two 45 KVA generators, four ice melting tanks and a hot bath. The hut, which is the first step toward making the Japanese Antarctic base a permanent one, was constructed by the multipurpose building and assembling method, a new technique developed by the Takenaka Building Research Institute in Tokyo. The generator hut is oval-shaped and is made mostly of aluminium sandwich panels. It has been so designed as to enable easy construction by only seven or eight men even on a very rough terrain. It is an assembly type structure weighing a total of seven tones. Since it will be the heart of the daily life at the Antarctic base, strongest emphasis was laid on the resistance to fire and cold. It has been designed to withstand maximum winds of 60 meters per second (134 miles per hour) and temperatures of 45 degrees below zero centigrade. departmental bulletin paper